Reconstructing the landscapes of slavery : a visual history of the plantation in the nineteenth-century Atlantic world - Tomich, Dale W., 1946-; Marquese, Rafael de Bivar, 1972-; Funes Monzote, Reinaldo, 1969-; Venegas Fornias, Carlos, 1946- (The University of North Carolina Press, 2021)
"Assessing a unique collection of more than eighty images, this innovative study of visual culture reveals the productive organization of plantation landscapes in the nineteenth-century Atlantic world. These landscapes-from cotton fields in the Lower Mississippi Valley to sugar plantations in western Cuba and coffee plantations in Brazil's Paraíba Valley-demonstrate how the restructuring of the capitalist world economy led to the formation of new zones of commodity production. By extension, these environments radically transformed slave labor and the role such labor played in the expansion of the global economy"--